Forestry Building, Alaska-Yukon-Pacific-Exposition, Seattle, Washington, 1909 - Weaver, Eugene M. (1909)
Handwritten on verso: Forestry. A.Y.P.E. PH Coll 772.2 To order a reproduction, inquire about permissions, or for information about prices see: http://www.lib.washington.edu/specialcollections/services/reproduction/reproduction Please cite the Order Number